A case report: anti-NMDA receptor encephalitis - Pavan Bhat; Ameer Ahmed; Preetam Jolepalem; Charmian Sittambalam (Greater Baltimore Medical Center, 2018)
N-methyl-d-aspartate receptor (NMDAR) antibody encephalitis is a potentially fatal autoimmune syndrome in which there is antibody production against the NMDAR causing profound dysregulation of neurotransmission. The syndrome is frequently associated with ovarian teratomas and women are disproportionately affected. Patients most often present with a constellation of neuropsychiatric signs and symptoms, including memory loss, hallucinations, and decreased level of consciousness. This condition is lethal if left untreated. Immunotherapy and surgical resection of the culprit malignancy often results in the rapid resolution of symptoms.